Zircon U-Pb dating and sulfide Re-Os isotopes of the Xiarihamu Cu-Ni sulfide deposit in Qinghai Province, northwestern China - Li Haoran, Li Haoran; Qian Ye, Qian Ye; Sun Fengyue, Sun Fengyue; Sun Jinlei, Sun Jinlei; Wang Guan, Wang Guan (Canadian journal of earth sciences, 2020)
The Xiarihamu Cu-Ni sulfide deposit is the second-largest Cu-Ni deposit in China, located in the Eastern Kunlun orogenic belt. However, despite previous study, the formation and evolution of this deposit remains a key unknown in the tectonic evolution of the Eastern Kunlun Orogenic Belt. Moreover, the petrogenesis of the ore-bearing rocks and the nature of ore genesis are the subjects of ongoing debate. Here, we present detailed field observations, petrology, zircon U-Pb geochronology, and Re-Os isotopic analyses to constrain the timing and genesis of the Xiarihamu Cu-Ni sulfide deposit. Sulfides from the massive ores yielded a Re-Os isotopic isochron age of 408 ± 11 Ma. Four samples from the ore-bearing Xiarihamu mafic-ultramafic intrusions yielded zircon U-Pb ages of 423.1 ± 2 Ma, 422.9 ± 3.1 Ma, 422.7 ± 2.3 Ma, and 422.6 ± 2.7 Ma, respectively, indicating that the ore formed during the Silurian. The calculated initial 187Os/188Os ratio and γOs values ranged from 0.5109 to 0.8499 and from 311 to 584, respectively, indicating that crustal contamination played an extremely important role in triggering sulfide saturation. In combination with previous research, drill core observations and Re-Os data provide robust evidence for multiple pulses of magma replenishment throughout the process of ore genesis. Based on this evidence, the large-scale magmatic Cu-Ni mineralization in Xiarihamu likely occurred in a post-collisional setting related to tectonic slab breakoff.